1990
DOI: 10.1111/j.1365-2621.1990.tb03572.x
|View full text |Cite
|
Sign up to set email alerts
|

Color Evaluation in Raw, Baked and Smoked Flesh of Rainbow Trout (Onchorhynchus mykiss) Fed Astaxanthin or Canthaxanthin

Abstract: Color of rainbow trout (Onchorynchus mykiss) was investigated using sensory and instrumental analysis. When judged in pairs with equal carotenoid concentration, astaxanthin caused less whiteness, higher chromaticity and more red hue of trout flesh than canthaxanthin. Sensory assessed whiteness, chromaticity and red hue significantly correlated with instrumental values for lightness, chromaticity and hue [CIE (1976) L*a*b* and H(°)ab]. Multivariate regression analysis improved the predictability for all sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
23
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 13 publications
12
23
0
Order By: Relevance
“…No effect of canthaxanthin concentration was observed on fillet lightness when processed with the gentle method. Similar results have been obtained with smoked fillets of rainbow trout fed diets containing either astaxanthin or canthaxanthin (Skrede, Storebakken, & Naes, 1990). Choubert et al (1992) reported that rainbow trout fed diets with astaxanthin were redder than fish fed diets with canthaxanthin.…”
Section: Effect Of Raw Materials Fat Content On Smoked Fillet Qualitysupporting
confidence: 78%
“…No effect of canthaxanthin concentration was observed on fillet lightness when processed with the gentle method. Similar results have been obtained with smoked fillets of rainbow trout fed diets containing either astaxanthin or canthaxanthin (Skrede, Storebakken, & Naes, 1990). Choubert et al (1992) reported that rainbow trout fed diets with astaxanthin were redder than fish fed diets with canthaxanthin.…”
Section: Effect Of Raw Materials Fat Content On Smoked Fillet Qualitysupporting
confidence: 78%
“…Changes in these parameters have also been reported in Atlantic salmon (Skrede and Storebakken, 1986) and in rainbow trout (Skrede et al, 1990). The smoking process caused visual changes in the flesh color of the trout which were fed the pigmented diets in accordance with results reported by Chen et al (1982).…”
Section: Cie Color In Smoked Fleshsupporting
confidence: 85%
“…Cooking trout reduces the pigmentation and may make the product less desirable for the consumer. Skrede et al (1989) analyzed the color in raw, baked, and smoked flesh of rainbow trout fed astaxanthin or canthaxanthin. They noted an increase in lightness and a slight decrease in redness and yellowness in baked trout.…”
Section: Objective Color Measurementsmentioning
confidence: 99%
“…The color of fish flesh is also affected by the storage and processing conditions, because most of the pigments are labile to heat, light, and oxygen (No and Storebakken, 1991;Skrede et al, 1989). Heating and freezing usually alter the red color and increase the lightness in food products.…”
Section: Introductionmentioning
confidence: 99%